Comprehensive evaluation of bone health using DXA and pQCT in an Indian boy with osteogenesis imperfecta - Karguppikar, Madhura Bharat (BMJ Case Rep, 2020)
We present a 9-year-old male child having history of fractures on trivial trauma with a family history of the same. He was treated for osteogenesis imperfecta (OI; zolendronate, calcium and vitamin D) and showed clinical improvement. On evaluating his bone health using dual energy X-ray absorptiometry and peripheral quantitative CT, we found that the child had bone density within the reference range but a smaller bone mass for his height, low muscle mass and thin bones with a lower strength strain index in comparison with healthy children. Our case suggests that treatment with bisphosphonates results in increase in bone density; however, bones remain thin and the lean body mass in these children may also be low. Controlled physical activity to improve muscle health and newer approaches to improve bone geometry would result in better bone health in children with OI.